2015
DOI: 10.1088/0957-4484/26/9/094002
|View full text |Cite
|
Sign up to set email alerts
|

Sub-nanometer dimensions control of core/shell nanoparticles prepared by atomic layer deposition

Abstract: , W. M. M. (2015). Sub-nanometer dimensions control of core/shell nanoparticles prepared by atomic layer deposition. Nanotechnology, 26(9), 094002-1/11. [094002]. DOI: 10.1088/0957-4484/26/9/094002 General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 59 publications
(97 reference statements)
1
59
0
Order By: Relevance
“…Weber et al demonstrated that when fabricating Pd@Pt core shell nanoparticles, the Pt shell thickness growth rate was 0.03 6 0.01 nm/cycle corresponding to $0.14 Pt atomic monolayer per cycle. 56 The results were similar to our findings. 13 In addition, the ALD methods are versatile since they allow for independent tuning of the core and shell diameter.…”
Section: Substrate Surface Modification With Samssupporting
confidence: 92%
See 2 more Smart Citations
“…Weber et al demonstrated that when fabricating Pd@Pt core shell nanoparticles, the Pt shell thickness growth rate was 0.03 6 0.01 nm/cycle corresponding to $0.14 Pt atomic monolayer per cycle. 56 The results were similar to our findings. 13 In addition, the ALD methods are versatile since they allow for independent tuning of the core and shell diameter.…”
Section: Substrate Surface Modification With Samssupporting
confidence: 92%
“…O 2 dissociation usually prefers to take place on a metal surface, leading to the formation of active oxygen atoms to decompose and activate MeCpPtMe 3 molecules for the following reactions. [55][56][57] Kessels and coworkers reported that when the O 2 partial pressure decreased to 7.5 mTorr, the growth of Pt on Al 2 O 3 was inhibited. 36 No Pt growth was observed on Al 2 O 3 surface even after 600 cycles.…”
Section: Core Shell Catalytic Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…This feature is especially attractive for the synthesis of heterostructured materials used in catalysis and nanodevices [362][363][364][365]. The ALD has also been explored as an alternative method for the preparation of advanced heterostructured and core-shell-structured electrocatalysts, such as Pd@Pt and Ni@Pt [368,374,[377][378][379][380]. For example, Cao et al [366] synthesized uniform Pd@Pt core-shell-structured electrocatalysts using the ALD technique with ODTS self-assembled monolayers as substrates (Fig.…”
Section: Principles and Development Of Atom Layer Depositionmentioning
confidence: 99%
“…sputtering, 1 radiolysis, 2 atomic layer deposition 3 ) and chemical (e.g. sputtering, 1 radiolysis, 2 atomic layer deposition 3 ) and chemical (e.g.…”
Section: Introductionmentioning
confidence: 99%